Hepatitis B in Sub-Saharan Africa - Jessica Howell; Nimzing G. Ladep; Maud Lemoine; Mark R. Thursz; Simon D. Taylor-Robinson (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2014)
Hepatitis B virus (HBV) infection causes a spectrum of acute and chronic liver disease, ranging from inactive chronic carrier status to progressive chronic hepatitis, leading to end-stage cirrhosis and primary liver cancer. In sub-Saharan Africa, over 8% of the population has chronic HBV carriage with a high risk for progressive liver disease. HBV-related hepatocellular carcinoma is the most common cancer among men and third most common among women. HBV therefore represents a critical threat to health in the African continent.